The relationship of plasma renin, angiotensin, and aldosterone levels to blood pressure variability and target organ damage in children with essential hypertension - Yang Liu; Yao Lin; Ming-Ming Zhang; Xiao-Hui Li; Yan-Yan Liu; Jing Zhao; Lin Shi (BMC Cardiovascular Disorders, 2020)
Abstract Background To investigate the relationships of plasma renin, angiotensin, and aldosterone levels to blood pressure variability and target organ damage in children with essential hypertension. Methods A case-control study was conducted on 132 children diagnosed with essential hypertension (103 males and 29 females with the mean age of 11.8 ± 2.4 years). The plasma RAAS levels were measured using the enhanced chemiluminescence method, the ambulatory blood pressure was monitored for 24 h, and then the average real variability (ARV) was calculated. Data on indicators were used for assessing cardiac and renal damages. The correlations of plasma renin, angiotensin, and aldosterone (RAAS) levels to blood pressure variability (BPV) and target organ damage (TOD) were studied. A comparison between the groups was conducted using SPSS 20. Results Among the 132 children, 55 cases had target organ damage. The 24-h ARV and the daytime ARV of the systolic blood pressure of the high angiotensin II (AT II) group was significantly higher than that of the normal AT II group (t = 2.175, P = 0.031; t = 2.672, P = 0.009). Plasma AT II and aldosterone levels were significantly associated with the left ventricular mass index (r = 0.329, P = 0.0001; r = 0.175, P = 0.045). Linear regression analysis showed that AT II [β ± s.e. = 0.025 ± 0.006, 95% CI (0.013–0.038), P = 0.0001] and aldosterone [β ± s.e. = 0.021 ± 0.007, 95% CI (0.008–0.034), P = 0.002] were risk factors for LVH. Conclusions The AT II level in children with essential hypertension affected the variability of the 24-h and the daytime SBP. Plasma AT II and aldosterone levels were associated with cardiac damage. Results from this study indicated that AT II and aldosterone are risk factors for LVH in childhood hypertension and are of great significance for improving the clinical prognosis of pediatric patients with hypertension.